Derivation of Operational Intervention Levels for the early phase of radioactive material at Koeberg Nuclear Power Station - Trollope, Ian Douglas (My University, 2015)
An investigation was performed to look at a method to develop easy to use field survey measurements to assist decision makers in the process of deriving public protective actions. This method could be used at a nuclear power plant if certain accident conditions are known. International values for operational intervention levels (OIL’s) do exist and are recommended to be employed if station specific data has not been derived. No values exist specific to Koeberg Nuclear Power Station and as a result, this became an ideal opportunity to derive station specific values. It was firstly necessary to decide on a specific accident type and hence an applicable accident release fraction. A suitable accident software dispersion code was applied to calculate the organ doses for the selected accident type. It was also decided to use two different wind dispersion criteria to further refine the results. Due to the complexities of dose distribution within the body it was also necessary to look at the gamma dose in isolation as this would be the measurement radiation type utilised as a limit in the field either using installed radiation monitors or by physical measurement performed by station Radiation Protection staff. Comparisons were done with thyroid and lung dose versus gamma dose to arrive at ratios for this specific accident type. This would then be indicative of the total dose to each organ as a result of a single field measurement. Conclusions were drawn on the results obtained and recommendations were made for when this type of data may be suitable for use in the unlikely event of a nuclear accident.
A research report submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science, Joannesburg, 2014.
Keywords: Nuclear power plants.; Power resources.; Radioactive substances.